KEPRAKTISAN ENSIKLOPEDIA FAMILI APOCYNACEAE KEBUN RAYA BANUA UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Feryna, Maulida; Zaini, Muhammad; Rezeki, Amalia (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
Development research is perfecting the product in accordance with product references and criteria, so as to produce a product that has been tested through various stages and validation. The development is in the form of an encyclopedia which is a type of teaching material that contains sources of information with text and illustrated images arranged systematically, designed according to learning objectives. The developed encyclopedia contains complete information about the apocynaceae family in the Banua Botanical Garden. This study aims to describe the practicality of the apocynaceae family encyclopedia in the Banua Botanical Garden. The research method used is Tessmer's formative evaluation design, which consists of: 1) expert review; 2) one-to-one; 3) small group evaluation; The individual test subjects were 4 students who took the phanerogamae course, and the small group test subjects were 4 students who took the phanerogamae course. The data were obtained from the research instrument practicality of content and practicality of expectations. The results showed that the practicality of the content scored 3.79 in the good category and the practicality of expectations earned a total score of 9.65% in the very good category. This shows that the encyclopedia of the apocynaceae family of the Banua Botanical Garden gave a positive response because it has attractiveness and is practical because it is easy to use.